The Impact of Augmented Reality Based on STEM Integrated Cognitive Conflict-Based Learning on Student Scientific Literacy, Motivation, and Retention - Fatni Mufit; Melisa Putri; Hidayati Hidayati; Selma Riyasni; Zahra Fathanah (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2025)
This research is motivated by the low science literacy, motivation and retention of students in learning physics, especially in Newton's law of gravity and Kepler's law. The use of teaching materials in schools has not been able to develop these three things optimally. This study aims to determine the effectiveness of the use of STEM-integrated cognitive conflict-based augmented reality on improving students' science literacy, motivation, and retention on Newton's law of gravity material. The method used is pre-experimental with a one-group pretest-posttest design, which involves one experimental class. The research sample consisted of 30 students in grade XI Phase F3 of SMAN. The instruments of this research are a critical thinking test and a motivation questionnaire. The results showed a significant improvement in students' science literacy skills, motivation, and retention after being given treatment, with the average science literacy score increasing from 48.00 to 75.33, and the motivation score from 2.51 to 3.83. The Wilcoxon test showed significant differences in the variables of science literacy and motivation. Student retention reached 81.95 percent, included in the very high category despite a decrease from posttest to retest. It can be concluded that the use of STEM-integrated cognitive conflict-based augmented reality is effective in improving students' science literacy, motivation, and retention